Lalat predator Coenosia humilis Meigen (Diptera: Muscidae) pada pertanaman kentang: pola aktivitas harian, pemangsaan, dan pengaruh aplikasi insekisida - Harwanto Harwanto; Dadan Hidayana; Nina Maryana; Aunu Rauf (Jurnal Entomologi Indonesia, 2004)
Field and laboratory studies were conducted on potatoes in pangalengan during April until October 2001, with the objectives to determine the daily activity pattern of the predatory fly Coenosia humilis Meigen (Diptera: Muscidae), to study the behavior of predator as well as level predation, and to evaluate effects of two cultural practices on population of flies. Our research revealed. that C. humilis were more active during morning and afternoon. Predatory flies attacked  by capturing the flying preys, and then sucked preys body content. The preys were generally small insects. About 60% of the preys were found to be agromyzed files, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae). In laboratory each predator consumed 23.5 leafminer flies per day. Insecticide application significantly suppressed the predator and at the same time promoted the leafminer population.